Neke posebnosti njemačkog jezika glede međunarodnog prometa robom i špedicije kao jezika struke - Fox, Renata (Promet - Traffic&Transportation, 2012)
On the example of the segment of German technical reading materials (professional publications, periodicals, bus mess correspondence) dealing with international goods turnover and forwarding the author has attempted a review of the so called 'special language'. Gennan as used in forwarding fits into the general concept of a special language (or technical language) to a major extent from lexical, syntactic and textual aspect. On the other hand it shows certain specific qualities: it makes a combination of a number of technical jargons: legal, administrative, engineering, commercial, financial and banking operations. The lexical elements of English are rather expressedly present. In the teaching process these specific aspects set the requirement for making use of professional publications, students' extra linguistic knowledge and their knowledge of other foreign languages.